Microstructural Evolution and Domain Engineering in Porous PZT Thin Films - Evgeny Zhemerov; Arseniy Buryakov; Dmitry Seregin; Maxim Ivanov (Surfaces, 2025)
Porous PZT films offer significant potential due to tunable electromechanical properties, yet the polarization behavior remains insufficiently understood because of discontinuous morphology and domain structures. In this work, we study the impact of porosity on the spontaneous polarization and electromechanical response of PZT thin films fabricated using a multilayer spin-coating technique with various concentrations (0–14%) of polyvinylpyrrolidone (PVP) as a porogen. Atomic force microscopy (AFM) and piezoresponse force microscopy (PFM) were employed to analyze the local topography, domain distribution, and polarization behavior of the films. The results indicate that increasing porosity leads to substantial changes in grain morphology, dielectric permittivity, and polarization response. Films with higher porosity exhibit a more fragmented polarization distribution and reduced piezoresponse, while certain orientations demonstrate enhanced domain mobility. Despite the decrease in overall polarization, the local coercive field remains relatively stable, suggesting structural stability during the local polarization switching. The findings highlight the crucial role of grain boundaries and local charge redistribution in determining local polarization behavior.